A Bayesian updating approach for bridge condition assessment using visual inspection data. (2016) - Dirbaz, Mojtaba; Modares, Mehdi; Mohammadi, Jamshid
This paper presents a new method for assessing the condition of a bridge. This method will hereafter be referred to as Bayesian Bridge Condition Assessment (BBCA). Using BBCA, first, the condition rating of a bridge is expressed using probability values in order to consider the uncertainties. Then, as new information for condition rating becomes available, the prior condition rating is updated to arrive at a posterior condition rating using Bayesian updating approach. This enhanced condition rating represents the up-to-date condition; and as such, it is expected to be a better representative of the condition of the bridge. Numerical illustrations are provided to demonstrate the applicability of the method to highway bridges. It is shown that the method described in this paper is especially applicable to bridges for which visual inspection data are compiled on a periodic basis.